Obscure face recognition using deep neural networks - Akash, MD Shahadat Hossain; Sharife, Shadman Bin; Datta, Bondon (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.